On potentialities to be lent from artworks (Palíndromo, 2023)
The present article intends to demonstrate the importance of mediation as an active derivation of curatorship in art exhibitions, highlighting the concepts associated with the actions of this nature, developed by the Divisão de Artes Plásticas da Casa de Cultura da Universidade Estadual de Londrina [Fine Arts Division of the Culture House of the State University of Londrina]. We chose the exhibition "Empresta-me um de seus dias" [Lend me one of your days], from the "Arte Londrina" [Art Londrina] public notice, and from it the work "Espaço para gerar espaço" [Space to generate space], by the artist Gabriel Bonfim, for the connections between artwork and mediation. Empathy, listening and performativity are concepts that guide the issues proposed here.
Keywords: Art exhibition; Mediation; Curation; Empathy; Contemporary art